Pengaruh Terapi Kombinasi Aromaterapi Lavender dan Dzikir Terhadap Penurunan Stres dan Tekanan Darah Pada Penderita Hipertensi - Taukhit; Rudi Haryono (Jurnal Keperawatan Notokusumo, 2018)
Background: World health agency (WHO) in 2012 showed 26.4% of people suffering from hypertension. One of the things that affect blood pressure is stress. Blood pressure can be lowered by lowering stress levels. Non- pharmacological efforts to reduce stress is with relaxation techniques, including aromatherapy lavender and dhikr. The purpose of this research is to know the influence of combination of aromatherapy lavender and dzikir to stress level and blood pressure of hypertension patient. Method: This research uses quasi experimental design with pretest-posttest intervention with control group. The sample was 30 respondents divided into 15 people of the intervention group and 15 control group. The intervention group received lavender aromatherapy and dhikr and antihypertensive therapy for 3 consecutive days while control group only received antihypertensive therapy. The analysis used paired t-test to determine the effect of intervention in the intervention group and independent t-test to see the difference between the influence between groups. Result: lavender and dhikr aromatherapy did not decrease stress score significantly with p = 0,925, mean also in decrease of systole blood pressure with p-value = 0,014 and not significant at decrease of diastole blood pressure with value p = 0,265. Conclusion: The combination of lavender aromatherapy and dhikr significantly decreased systole blood pressure. Whereas for stress and diastolic blood pressure, such combination therapy may be decreased but statistically insignificant.